2022
DOI: 10.7554/elife.83037
|View full text |Cite
|
Sign up to set email alerts
|

Human Dectin-1 is O-glycosylated and serves as a ligand for C-type lectin receptor CLEC-2

Abstract: C-type lectin receptors (CLRs) elicit immune responses upon recognition of glycoconjugates present on pathogens and self-components. While Dectin-1 is the best-characterized CLR recognizing b-glucan on pathogens, the endogenous targets of Dectin-1 are not fully understood. Herein, we report that human Dectin-1 is a ligand for CLEC-2, another CLR expressed on platelets. Biochemical analyses revealed that Dectin-1 is a mucin-like protein as its stalk region is highly O-glycosylated. A sialylated core 1 glycan at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Interestingly, dectin-1 causes platelet activation without triggering thrombus formation. [224] Finally, the snake venom protein rhodocytin is an endogenous protein-ligand for CLEC-2 that triggers rapid platelet activation and aggregation. [238] The interaction of the rhodocytin α-subunit and CLEC-2 is carbohydrate-independent as rhodocytin is not glycosylated but essentially utilizes the same surface as PDPN.…”
Section: Example 5: Clec-2mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, dectin-1 causes platelet activation without triggering thrombus formation. [224] Finally, the snake venom protein rhodocytin is an endogenous protein-ligand for CLEC-2 that triggers rapid platelet activation and aggregation. [238] The interaction of the rhodocytin α-subunit and CLEC-2 is carbohydrate-independent as rhodocytin is not glycosylated but essentially utilizes the same surface as PDPN.…”
Section: Example 5: Clec-2mentioning
confidence: 99%
“…[110,[223][224][225][226][227][228][229] Although the exact binding mode of most protein ligands for dectin-1 is still an open question, the interaction of human dectin-1 with CLEC-2 has been mapped to a distinct interactions motif in the stalk of dectin-1 and binding sites of annexins and angiotensin II appears to be different from the binding site of βglucan. [110,224,226] Dectin-1 illustrates how a binding site distinct from canonical Ca 2 + -dependent carbohydrate recognition site mediates glycan binding and becomes the primary binding site for the role of dectin-1 as a pattern recognition receptor. Moreover, the existence of multiple protein ligands with potentially more distinct binding sites underlines the functional variability of the CTLD fold.…”
Section: Example 3: Mglmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that GPVI and CLEC-2 are pattern recognition receptors (PRRs) 34 because, aside from PDPN and collagen, multiple endogenous and exogenous substances bearing electrically charged moieties interact with them and activate platelets. 13,35,36 Recent studies have also identified dual activators of CLEC-2 and GPVI; heme and galectin-9 bind to both CLEC-2 and GPVI and activate platelets. 37,38 Given the nature of PRRs, it is not surprising that some small molecules can prevent both receptors from binding their respective ligands.…”
Section: Difference In Effective Inhibitory Concentrations Between Pr...mentioning
confidence: 99%
“…Beta-glucan is receiving attention as an immune modulator without compromising the production performance and has no undesirable effects on birds (Cox et al, 2010). Linear forms of β-glucan have attained more interest from researchers for high production and bioavailability instead of branched ones because the primary innate immune receptors for 1-3 β-glucan are dectin-1 which are entirely expressed in monocytes (Haji et al, 2022).…”
Section: Introductionmentioning
confidence: 99%